Toward defining plasma treatment dose: The role of plasma treatment energy of pulsed‐dielectric barrier discharge in dictating in vitro biological responses. Issue 3 (28th October 2021) - Lin, Abraham; Biscop, Eline; Gorbanev, Yury; Smits, Evelien; Bogaerts, Annemie
Abstract: The energy dependence of a pulsed‐dielectric barrier discharge (DBD) plasma treatment on chemical species production and biological responses was investigated. We hypothesized that the total plasma energy delivered during treatment encompasses the influence of major application parameters. A microsecond‐pulsed DBD system was used to treat three different cancer cell lines and cell viability was analyzed. The energy per pulse was measured and the total plasma treatment energy was controlled by adjusting the pulse frequency, treatment time, and application distance. Our data suggest that the delivered plasma energy plays a predominant role in stimulating a biological response in vitro. This study aids in developing steps toward defining a plasma treatment unit and treatment dose for biomedical and clinical research. Abstract : The impact of total plasma treatment energy on chemical species generation and cancer cell viability was investigated in vitro using a microsecond‐pulsed dielectric barrier discharge system. The total treatment energy encompasses the influence of plasma application parameters: pulse frequency, treatment time, and application distance. The results presented here represent strategic steps toward standardizing plasma treatment and dose.